Prototipe Sistem Keamanan Ruangan Menggunakan Finger Print dan Keypad Matrix dengan One Time Pad - Rahmita Pasmah; Abdul Jabbar Lubis; Ari Usman (Forum Kerjasama Pendidikan Tinggi, 2021)
The room security system design uses finger print and a matrix keypad with One Time Pad (OTP) in the Dean's room, Faculty of Engineering and Computers at Universitas Harapan Medan because it still uses conventional security. With security that is not always maintained, especially outside working hours, the authors make a room security system design to open the room only with registered fingerprints and programmed active telephone numbers, so that it cannot be accessed by others. This design is made with several components, namely Arduino as a data processor for the entire work system, the fingerprint reader functions to recognize the fingerprints to be registered, to enter the OTP code using the matrix keypad, Liquid Crystal Display (LCD) to display the data provided by Arduino through the program. that has been made, the relay is used to activate the solenoid, the solenoid functions to open or lock the door, the buzzer will sound when the fingerprint and password are not read, the GSM SIM900A module functions to send an OTP code using an active cell phone number, and the MC-38 magnetic sensor to know if the door is open or still closed. From this test it can be concluded that only the fingerprints of people who have been registered and the telephone numbers that have been programmed to be able to open the door of the room. If the fingerprint pattern is not registered then an alarm will sound